A review on steroid dimers: 2011-2019 - Nahar, Lutfun; Sarker, Satyajit D (Steroids, 2020)
The first review article on steroid dimers by Li and Dias in 1997, followed by the second review and a book on steroid dimers by Nahar and Sarker in 2007 and 2012, respectively, covered steroid dimers reported until the end of 2010. Since then, there have been considerable amounts of research carried out on steroid dimers, prompting the need for another comprehensive review on this topic. Therefore, this present review appraises the literature published during the period 2011-2019 on various aspects of steroid dimers, including isolation from natural sources, synthesis and applications. A structured and systematic literature search was performed, using the key words: steroid dimer, steroidal dimer, dimeric steroid, bis-steroid, bis-steroidal conjugates, molecular umbrella, cephalostatins, ritterazines and crellastatins. Several databases like Web of Knowledge, Science Direct, PubMed and Google Scholar were consulted. During the period covered in this review, well over 200 new synthetic steroidal dimers, ring A-ring A connection being the major group, have been reported, only one natural steroid dimer has been isolated, and potential applications of steroid dimers in the treatment of cancers and tumors, and microbial infections have been indicated.
Keywords: Anticancer; Steroids dimer; Synthesis; Natural products; Steroids; Molecular umbrella; Ritterazines; Crellastatins; dimerizace; antiinfekční látky; Antineoplastic Agents; Dimerization; Bis-steroid; protinádorové látky; Cephalostatins; steroidy; Anti-Infective Agents